Analysis of Students’ Errors in Solving Concept Understanding Problems On Integral Matter - Faradiba Jabnabillah (Mathematics Education Journal, 2022)
The ability to understand students' concepts is very important to be applied to learning mathematic. When students cannot understand the concept well, students will not be able to solve the problem correctly. This is the reason the researcher conducted this research. The purpose of this research is to describe student errors in solving problems of understanding the concept of integral material. The subjects in this study were class XII students of SMK N 4 Batam. The data collection technique used a test to see student errors in answering questions of understanding the concept. This study uses a qualitative approach with a descriptive type of research. The results obtained in this study are the indicators of reading errors about getting a percentage of 62,5%, then the percentage of errors in understanding the problem gets a value of 50%, the percentage of transformation errors gets a value of 75%, then on the percentage of process skills errors it gets a value of 62,5%, and the percentage of errors in writing the final answer also gets the same result as the percentage process skill error that is equal to 62,5%. This is because most students do not understand the integral concept so they do not understand in determining the formula and applying it.